Is the vertex a good control stimulation site? Theta burst stimulation in healthy controls - Pizem, Dominik; Novakova, Lubomira; Gajdos, Martin; Rektorova, Irena (Journal of neural transmission, 2022)
The vertex has been used as a suitable control stimulation site in repetitive transcranial magnetic stimulation studies. The objectives of this study are (1) to assess cognitive performance (CP) after theta burst stimulation (TBS); (2) to evaluate whether clinically relevant cortical areas might be reached by vertex stimulation and how that might influence CP. Twenty young healthy subjects performed a cognitive task prior to and immediately after intermittent TBS (iTBS) and continuous TBS (cTBS) of two active cortical stimulation sites and the vertex. We used the Wilcoxon signed-rank test to compare the pre- and post-stimulation reaction times (RTs) and a mixed ANOVA analysis to evaluate the effect of the stimulation on changes in RTs. A three-dimensional finite-element model (FEM) was used to calculate the vertex TBS-induced electrical field (E-field) in the adjacent regions of interest (ROIs). Correlation analyses were performed between E-fields in the ROIs and cognitive outcomes. We found a significant effect only of the stimulation time factor (F (1,12) = 65.37, p < 0.001) on RT shortening, with no superiority of the active site stimulation compared to the vertex stimulation. In 73.5% of vertex TBS sessions, a significant E-field was induced in at least one ROI. We found a negative association between the magnitude of the iTBS-induced E-fields and RT changes (R = - 0.54, p = 0.04). TBS protocols may lead to changes in CP when applied over the craniometrically targeted vertex. We therefore suggest not using a conventional approach as a vertex targeting method.
Keywords: theta rytmus EEG; Reaction Time; Transcranial Magnetic Stimulation; lidé; hlava; transkraniální magnetická stimulace; Head; Theta Rhythm; reakční čas; Humans